2012
DOI: 10.1002/hrm.21466
|View full text |Cite
|
Sign up to set email alerts
|

Training older workers: Lessons learned, unlearned, and relearned from the field of instructional design

Abstract: Changing workforce demographics have highlighted the need to provide training and development opportunities for older workers. This article critically examines the current state of research on the use of systematic instructional design procedures to develop work‐related training that is inclusive of older workers. The review reveals a disconnect between what the literature recommends to achieve age‐inclusive design and what is offered as evidence of age‐inclusive design. Age‐related generalizations about cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…Reduced button size has been shown to result in increased time on tasks and higher mental workload for older users ( Fezzani et al, 2010 ). In addition, given their age-related changes, effective technology-based training for older workers should be self-paced, highly structured, and incorporate a user-friendly and consistent interface to enhance learning outcomes ( Williams van Rooij, 2012 ; Wolfson et al, 2014 ). These design issues in emerging workplace innovations create potential systematic barriers for older workers’ performance, and may hamper their confidence and motivation to fully utilize technology.…”
Section: Time-related Changes In Jobsmentioning
confidence: 99%
“…Reduced button size has been shown to result in increased time on tasks and higher mental workload for older users ( Fezzani et al, 2010 ). In addition, given their age-related changes, effective technology-based training for older workers should be self-paced, highly structured, and incorporate a user-friendly and consistent interface to enhance learning outcomes ( Williams van Rooij, 2012 ; Wolfson et al, 2014 ). These design issues in emerging workplace innovations create potential systematic barriers for older workers’ performance, and may hamper their confidence and motivation to fully utilize technology.…”
Section: Time-related Changes In Jobsmentioning
confidence: 99%
“…Such demographics raise multiple questions in relation to the future global workforce composition. But the trend toward elderly employment continues and so does the interest of the scholarly community over the ways in which a “graying workforce” is best managed and motivated (Williams van Rooij, 2012; Tempest et al , 2002; Armstrong-Stassen and Schlosser, 2010; Calvano, 2013; Kanfer and Ackerman, 2004). Most indicative of the management science’s interest in employment of older workers is the August 2014 editorial of the Academy of Management Journal that was devoted to the effects of the aging population on management (Kulik et al , 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Another study poited out that training, in the use of technologies, should provide a lot of time for the practice of the trained functions and a supportive environment, through the combination of classroom-based and individual approaches (Chiu et al, 2016). In a review study that sought to critically examine the current state of research on the use of systematic instructional design procedures to develop job-related training for older workers (Van Rooij, 2012). Focusing only on studies that contained a pre-test/post-test study project with reported effect sizes, the author found that small-group training or those that took into account each participant's learning pace were related to high levels of performance when compared to trainings performed in large groups and in a different pace than the worker's receiving the training.…”
Section: Ict Training Of Older Brazilian Workersmentioning
confidence: 99%
“…Focusing only on studies that contained a pre-test/post-test study project with reported effect sizes, the author found that small-group training or those that took into account each participant's learning pace were related to high levels of performance when compared to trainings performed in large groups and in a different pace than the worker's receiving the training. In addition, evidence indicates that older workers perform well in training, especially when they are guided considering the reality of each worker, age issues, their previous knowledge, skills, goals, attitudes, motivation, values and interests (Ilmarinen, & Ilmarinen, 2015;Beier, 2015;Czaja, Sharit, 2012;Van Rooij, 2012).…”
Section: Ict Training Of Older Brazilian Workersmentioning
confidence: 99%
See 1 more Smart Citation